Pembuatan Sistem Informasi untuk Divisi Marketing PT. Diparanu Rucitra - Ignatius Dwihan Prajogo; Silvia Rostianingsih; Alexander Setiawan (Jurnal Infra, 2018)
PT. Diparanu Rucitra located at Surabaya, as property developer, all of documents are stored in physical documents, and Microsoft Excel for every work they do. This may causes searching documents very difficult and spend lot of time because still uses manual system, difficult to record all work from marketing division, especially when they held event, looking new customer, sales order, property sales and property payment along with all reports.This application created using HTML5, PHP, Javascript, CSS3, framework PHP and database MySQL. Application interface is created using Bootstrap Template Pooled Admin panel.The final result of this application is make all job more integrated and structural from got new customer, sales order, property sales and property payment along with created/ongoing/ended event for this marketing division at PT. Diparanu Rucitra.